Red blood cell distribution width and the risk of being in poor glycemic control among patients with established type 2 diabetes - Yin YQ; Ye SS; Wang HB; Li B; Wang AP; Yan WH; Dou JT; Mu YM (Dove Medical Press, 2018)
Yaqi Yin,1,* Sisi Ye,2,* Haibin Wang,1 Bing Li,1 Anping Wang,1 Wenhua Yan,1 Jingtao Dou,1 Yiming Mu1 1Department of Endocrinology, Chinese PLA General Hospital, Beijing, People’s Republic of China; 2Department of Medical Oncology, Chinese PLA General Hospital, Beijing, People’s Republic of China *These authors contributed equally to this work Background: The red cell distribution width (RDW) has been shown to be associated with the incidence and complications of type 2 diabetes (T2D). However, the relevance of RDW with the risk of being in poor glycemic control among patients with established T2D is largely overlooked. Methods: A total of 702 T2D participants from the REACTION study were enrolled in this study. Blood routine index, fasting plasma glucose, hemoglobin A1c and lipid profile data were available for all of the enrolled population. Results: The univariate logistic analysis revealed a significant association between RDW and the risk of being in poor glycemic control among T2D subjects with an odds ratio (OR) and a 95% confidence interval (CI) of 0.5 and 0.3–0.8, respectively, for the fourth vs the first quartile of RDW. The association strengthened after multivariable adjustment (OR [95% CI]: 0.3 [0.2–0.7]). Interaction and stratified analyses indicated that this association was seen only among T2D subjects with lower body mass index and/or serum lipid levels. Conclusion: T2D patients with higher RDW had significantly lower risk of being in poor glycemic control. RDW may contribute to risk assessment for T2D individuals at risk of being in poor glycemic control. Keywords: type 2 diabetes, red cell distribution width, glycemic control